2009 3DTV Conference: The True Vision - Capture, Transmission and Display of 3D Video 2009
DOI: 10.1109/3dtv.2009.5069629
|View full text |Cite
|
Sign up to set email alerts
|

Mixed resolution coding of stereoscopic video for Mobile devices

Abstract: This paper presents results for full and mixed resolution stereo video coding including subjective and objective evaluation for 3DTV on Mobile devices. For this, objective as well as subjective tests have been carried out with different sequences at different image sizes and evaluated on two different stereoscopic displays. The subjective tests showed, that for uncoded sequences full resolution was rated better, however for coded sequences at low bit rates mixed resolution was rated better. An unsharp masking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
2
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 5 publications
1
33
2
3
Order By: Relevance
“…The impact of quantization was verified in [4], which concluded that the perceived quality of coded equal-resolution stereo image pairs was approximately the average of the perceived qualities of the high-quality image and the low-quality image of the stereo pairs. A subjective evaluation for fulland mixed-resolution stereo video coding on a 32-inch polarization stereo display and on a 3.5-inch mobile display was presented in [5]. The results revealed that fullresolution (FR) was rated better for uncoded sequences in 79% of the test cases, while MR where one of the views was downsampled to a quarter resolution was rated better in 57% of the test cases for H.264/AVC-coded sequences.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of quantization was verified in [4], which concluded that the perceived quality of coded equal-resolution stereo image pairs was approximately the average of the perceived qualities of the high-quality image and the low-quality image of the stereo pairs. A subjective evaluation for fulland mixed-resolution stereo video coding on a 32-inch polarization stereo display and on a 3.5-inch mobile display was presented in [5]. The results revealed that fullresolution (FR) was rated better for uncoded sequences in 79% of the test cases, while MR where one of the views was downsampled to a quarter resolution was rated better in 57% of the test cases for H.264/AVC-coded sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Dancer 960x540 480x270 360x202 240x135 Dog 800x600 400x300 300x225 200x150 Pantomime 800x600 400x300 300x225 200x150 Champagne 800x600 400x300 300x225 200x150 Newspaper 768x576 384x288 288x216 192x144 experiment was generally higher than in [3]. The exact values for pixels per viewing angle could not be concluded from the information given in [4], but it discovered equivalently the subjective difference between FR and MR was a descending function of the viewing distance or the resolution in terms of number of pixels. We also analyzed whether the subjective image quality ratings had a correlation to the average luma peak signal-to-noise ratio (PSNR) of the lower resolution view.…”
Section: Limit Of Downsampling Ratiomentioning
confidence: 94%
“…The study presented in [4] included a subjective evaluation for full-and mixed-resolution stereo video on a 32-inch polarization stereo display and on a 3.5-inch mobile display. One of the views in the MR sequences was downsampled to a half resolution both horizontally and vertically.…”
Section: Introductionmentioning
confidence: 99%
“…Taking the bitrate for the left view as given for 2D video, the 3D video functionality could be added by an overhead of 25-30% for coding the right view at quarter resolution. Such and similar approaches are currently under investigation [5]. A general drawback of CSV is that the 3D impression cannot be modified.…”
Section: Stereo Simulcast and Interleavingmentioning
confidence: 99%